If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + (-10) = 2 q + -10 = 2 Reorder the terms: -10 + q = 2 Solving -10 + q = 2 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + q = 2 + 10 Combine like terms: -10 + 10 = 0 0 + q = 2 + 10 q = 2 + 10 Combine like terms: 2 + 10 = 12 q = 12 Simplifying q = 12
| (y/4)=-7 | | p-8/(1/2)=-3 | | 100g=20 | | 72n=9 | | (2x+3)+(-3x+1)= | | -8/1/2=-3 | | -6x+3=-20 | | 10x-6=7-12 | | x+5.1+9.4=18.2 | | x+5.1+9.5=18.2 | | x-85=-5+-7 | | 24a-12ab= | | X^2+9x-234=0 | | 3x-4y-16=o | | -2/3*-3+5 | | (-2/3x-3)+5 | | X/5=49 | | x+4-2x=14 | | 1/4(x+2)-2=0.5 | | -2/3x-3+5 | | 7=-2/3x-3+5 | | -3=-2/3x+5 | | 10x=16+4x | | 10x-10=4x-10 | | (6)4+25= | | R/2=9 | | 4x+56=18x | | 9w-13x=25 | | 4-(y+9)=10 | | w=-275(2(1)-7) | | 15x-10-6x=1 | | Y=50x+1 |